Identification of Novel Natural Products as Effective and Broad-Spectrum Anti-Zika Virus Inhibitors - Gao, Yaning (Viruses, 2019)
Zika virus (ZIKV) infection during pregnancy leads to severe congenital Zika syndrome, which includes microcephaly and other neurological malformations. No therapeutic agents have, so far, been approved for the treatment of ZIKV infection in humans; as such, there is a need for a continuous effort to develop effective and safe antiviral drugs to treat ZIKV-caused diseases. After screening a natural product library, we have herein identified four natural products with anti-ZIKV activity in Vero E6 cells, including gossypol, curcumin, digitonin, and conessine. Except for curcumin, the other three natural products have not been reported before to have anti-ZIKV activity. Among them, gossypol exhibited the strongest inhibitory activity against almost all 10 ZIKV strains tested, including six recent epidemic human strains. The mechanistic study indicated that gossypol could neutralize ZIKV infection by targeting the envelope protein domain III (EDIII) of ZIKV. In contrast, the other natural products inhibited ZIKV infection by targeting the host cell or cell-associated entry and replication stages of ZIKV. A combination of gossypol with any of the three natural products identified in this study, as well as with bortezomib, a previously reported anti-ZIKV compound, exhibited significant combinatorial inhibitory effects against three ZIKV human strains tested. Importantly, gossypol also demonstrated marked potency against all four serotypes of dengue virus (DENV) human strains in vitro. Taken together, this study indicates the potential for further development of these natural products, particularly gossypol, as the lead compound or broad-spectrum inhibitors against ZIKV and other flaviviruses, such as DENV.